PENGUATAN KOMPETENSI PEMASARAN PELAKU UMKM KECAMATAN CITAMIANG MELALUI EDUKASI DAN PENDAMPINGAN BISNIS BERKELANJUTAN - Sugih Prakoso; Sandi Setiadi (PT. ABIG RIZKY PUBLISHER, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in Citamiang District possess significant economic potential; however, they continue to face critical challenges in the marketing aspect. Most business actors in this area still rely on word-of-mouth promotion strategies, have limited digital marketing literacy, encounter difficulties in branding, and have not received sustainable business assistance. Therefore, this Community Service Program (PkM) aims to strengthen the marketing competencies of local MSME actors through educational programs and sustainable business mentoring. The program was implemented using a Participatory Action Research (PAR) approach, which emphasizes the active participation of business partners. The implementation stages included field observations to identify problems, socialization activities, Focus Group Discussions (FGDs), and offline mentoring sessions. The outcomes of this program were realized through four main areas of assistance: modern marketing strategy training, digital marketing training, branding and product development assistance, and long-term business consultation. The program received enthusiastic responses from participants and is expected to assist MSMEs in Citamiang in adopting digital technologies, expanding market access, and enhancing their business competitiveness and sustainability.